Faktor-Faktor Yang Mempengaruhi Produksi Jagung Di Kelurahan Tendeki Kecamatan Matuari Kota Bitung - Nainggolan, Jessika Karunia; Kapantow, Gene Henfried Meyer; Dumais, Joachim Noch Karel (AGRI-SOSIOEKONOMI, 2023)
This study aims to analyze the factors that influence corn production in Tendeki Village, Matuari Subdistrict, Bitung City. The research was conducted in September 2022 with a predetermined research site in Tendeki Village, Matuari District, Bitung City. The data collection method is the survey method. Interview data collection techniques using questionnaires. The analysis method used in this study uses multiple linear regression methods so that the analysis used refers to the formulation of research objectives. By using the model of the Cobb-Douglass production function, R2 test, multicollinearity test, f test, and t test. The results of this study indicate that the variables of land area, seeds, urea fertilizer, NPK fertilizer affect the amount of corn production in Tendeki Village, Matuari District, Bitung City. Partially, the factors of land area, urea fertilizer, and labor have a positive effect, and the number of seeds has a negative effect, while NPK fertilizer has no significant effect.